Testing of Superiority and Resistance of Cayenne Pepper of Blaze 12 Variety to Pepper Yellow Leaf Curl Disease - Kustanto, Heri (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2022)
Cayenne pepper is one of the important vegetables and has high economic value. This plant can be cultivated in various types of soil in the lowlands to the highlands. Chilies are very much liked by Indonesian people because of it is spicy and contains various nutrients and vitamins. The purpose of this study was to study and determine the productivity and resistance to yellow curly leaf disease of Blaze 12 varieties compared to comparison varieties. The demand for chili continues to increase from year to year but chili production is not optimal. Efforts to increase crop production have several obstacles related to seed quality, crop cultivation technique, pest and disease attacks. Pepper yellow leaf curl virus (PYLCV) is a disease that can reduce production and cause crop failure. One of the ways to improve seed quality is through a breeding process to support chili productivity and improve other characters such as resistance to disease.Testing of variety is a final stage in plant breeding before varieties are released and commercialized. The purpose of this study was to study and determine the productivity and resistance to yellow curly leaf disease of Blaze 12 varieties compared to comparison varieties. The results of the analysis variance showed a significant effect on the characters: leaf length, leaf width, fruit length, fruit diameter, skin thickness, weight per fruit, number of fruit per plant and yield per hectare. Resistance to yellow curl leaf disease of the Blaze 12 variety was as same as VP-3 and better than VP-1 and VP-2, which showed resistance with mild symptoms. The character of cayenne pepper yellow curl disease is closely related to leaf area.